1,5-DILITHIATED ARENES - DOUBLE METAL BRIDGING VERIFIED BY 3 X-RAY STRUCTURES AND MNDO CALCULATIONS - Hampel, Frank; Clark, Timothy; Kos, Alex; Schleyer, Paul; et al. (Journal of the American Chemical Society, 1993)
The crystal structures of three 1,5-doubly lithium bridged heteroatom-linked diaryl systems with sulfur (4), oxygen (5), and nitrogen (6) as flexible centers have been determined. All are monomers in the crystals. Each lithium bridges both deprotonated ortho carbons symmetrically. The coordination sphere of the metal is completed by the bidentate ligand tetramethylethylenediamine (TMEDA). The pi-system is coplanar in o,o'-bis(lithio.TMEDA)diphenyl thioether (4b), but the rings are tilted markedly in o,o'-bis(lithio.TMEDA)diphenyl ether (5b) and in 1,2'-bis(lithio.TMEDA)-N-phenylcarbazole (6b). The distance between the metalated carbons is responsible for the degree of twisting of the phenyl rings. The structural features of 4b and 6b are reproduced well by MNDO calculations (with ethylenediamine (EDA) (4a-6a) as a model for TMEDA), but less so for the oxygen derivative 5b. MNDO emphasizes the thermodynamic preference for double lithium bridging in o,o'-dilithiated diphenyl systems. The MNDO relative energies of 4a-6a agree well with ab initio results with regard to the stabilization effects of each of the three heteroatoms ortho to a negative charge. Gilman's claim that N-phenylcarbazole gave the o,o'-dilithiated-N-phenyl product could not be confirmed; instead, one of the adjacent sites on the carbazole ring is metalated. The principle of symmetrical doubly lithium bridging has been evaluated computationally (MNDO) for two aromatic systems dilithiated in the 1,4-positions. The symmetrically doubly bridged rotamer of o,o'-bis(lithio.EDA)biphenyl (9a')(with perfectly coplanar pi-systems) is 8.8 kcal/mol more stable than the isomer with perpendicular phenyl rings (9a''). Steric proximity of H8/H8' in doubly bridged 2,2'-bis(lithio-EDA)-1,1'-binaphthyl (10a') prevents coplanarity of the naphthyl moieties. A slight preference (0.7 kcal/mol) for the perpendicular conformation (10a'') results. While the pi-systems are not coplanar in 10a', this is compensated by the tilting of the naphthyl moieties. Thus, the distance between both anionic centers in 10a' is still appropriate for lithium double bridging. X-ray structures of 5b and 6b and the MNDO geometry of 10a emphasize the preference for symmetrical double lithium bridging, even if the pi-systems are twisted.